Использование суперконденсаторов в частотно-регулируемом электроприводе - Браславский, Исаак Яковлевич; Ишматов, Закир Шарифович; Плотников, Юрий Валерьевич; Полунин, Федор Анатольевич (НТУ "ХПИ", 2013)
The questions connected with the investigation of new type of frequency-controlled electric drive with capacitive energy storages are considered. The experimental investigation results of transients and energy characteristics of electric drive with ultracapacitors are shown.
Keywords: проблема энергосбережения; электроэнергия; преобразователи частоты; емкостные накопители энергии; экспериментальные исследования; интенсивный повторно-кратковременный режим